Comparison of the Effectiveness of Schema Therapy-Based Couple Therapy and Emotionally Focused Couple Therapy on Attachment Behaviors in Incompatible Couples - Besharatmehr, Neda; Jahangiri, Mohammad Mehdi; Taghvaei, Davood (Psychology of Woman Journal, 2025)
Objective: This study aimed to compare the effectiveness of schema therapy-based couple therapy and emotionally focused couple therapy on attachment behaviors in incompatible couples.Methods and Materials: The research employed a quasi-experimental design with a pre-test, post-test, control group, and a two-month follow-up period. The statistical population included all couples who sought psychological and counseling services in Tehran in 2023. Using purposive sampling, 45 couples who met the inclusion criteria were selected and randomly assigned to three equal groups (15 couples per group). Data were collected using the Spanier Marital Adjustment Questionnaire (1976) and the Accessibility, Responsiveness, and Companionship Questionnaire by Sandberg et al. (2012). Participants in the experimental groups received therapeutic interventions over 10 weekly sessions, each lasting 90 minutes, while the control group did not receive any interventions. Data were analyzed using repeated-measures analysis of variance (ANOVA).Findings: The results indicated that both schema therapy-based couple therapy and emotionally focused couple therapy significantly increased attachment behaviors in incompatible couples compared to the control group (p < 0.05).Conclusion: Given the effectiveness of these therapeutic approaches, psychologists and counselors working in this field are recommended to utilize these intervention methods to enhance attachment behaviors in couples experiencing incompatibility.